Compact tapered slot UWB antenna with WLAN band rejection - Medeiros, Carla R. (2014)
This letter extends the design of a previously proposed uniplanar ultrawideband (UWB) antenna to include within its 3.110.6-GHz operation band a rejection of the wireless local area network (WLAN) band near 5.5 GHz. The antenna configuration is based on a combination of two crossed exponentially tapered slots plus a star-shaped slot printed on both sides of a 10-mils dielectric substrate. The band rejection is obtained with the addition of extra slots at the antenna back-face metallization. The radiation pattern and polarization are very stable over the entire UWB. Link measurements between two identical antennas demonstrate low pulse distortion over almost all the solid angle.